Visual assistance may impede sensorimotor learning during gamified rehabilitation exercises - Huang, Yuxuan; Elangovan, Naveen; Konczak, Jürgen; Interrante, Victoria (Frontiers in Virtual Reality, 2025)
Regular exercise is critical to post-stroke recovery, but can be frustrating and difficult for patients with limited motor capabilities. Robotic assistance devices are being used to support this process, but due to cost and accessibility concerns some researchers have drawn inspiration from virtual reality and proposed the use of what we call “visual-only assistance”, in which a patient’s physical movements are mapped into game-oriented visual feedback modified towards greater success in the gameplay objectives. Our concern is that the motivational benefits it provides may come at the cost of reduced sensorimotor learning, which could ultimately be counterproductive to the recovery process. To explore these concerns, we conducted a between-subjects study with 24 participants to examine how two types of visual-only assistance affect short-term proprioceptive skill learning in a motor training game involving airplane steering with wrist rotation. One group experienced “attractor assistance”, in which the airplane was continuously displaced toward an ideal position and orientation. The other experienced “tunnel assistance”, in which direct user control was maintained unless straying too far, triggering an invisible barrier. We hypothesized that motor learning would be more impeded with attractor assistance due to the constant mapping variation between physical movements and visual feedback, but our experiment found that motor learning did not materialize in either condition, suggesting that substituting intermittent visual assistance for constant visual assistance is insufficient to guarantee superior motor learning outcomes and that, pending further investigation, the use of visual assistance for proprioceptive training should continue to be regarded with caution.